Forecasting inflation and the inflation risk premiums using nominal yields - Bruno Feunou; Jean-Sébastien Fontaine (Bank of Canada, 2012)
We provide a decomposition of nominal yields into real yields, expectations of future inflation and inflation risk premiums when real bonds or inflation swaps are unavailable or unreliable due to their relative illiquidity. We combine nominal yields with surveys of inflation forecasts within a no-arbitrage model where conditional expectations are latent but spanned by the history of the observed data, analog to a GARCH model for the conditional variance. The filtering problem is numerically trivial and we conduct a battery of out-of-sample comparisons. Our favored model matches the quarterly inflation forecasts from surveys and uses the information in yields to produce the best monthly forecasts. Moreover, we restrict the distribution of the inflation Sharpe ratios to achieve economically reasonable estimates of the inflation risk premium and of the real rates. We find that the inflation risk premium (i) is positive on average, (ii) rises when the unemployment rate increases and (iii) when the level of interest rates decreases. Hence, real yields are more pro-cyclical than nominal yields due to variations of the inflation risk premiums.
Keywords: E43; E47; G12; 330; Asset pricing; Econometric and statistical methods; Interest rates; Inflation and prices